Some physical and mechanical properties of particle boards produced from industrial wood chips and Scots pine (Pinus sylvestris) cones - Karahan, Selim; Guler, Cengiz (Maderas. Ciencia y Tecnología, 2025)
This study investigated the potential use of Scots pine cones as an alternative raw material to larch wood chips for particle board production. Due to the increasing scarcity of forest resources, exploring alternative raw material for the forest industry has gained importance in in recent years. Particle boards were produced in laboratory conditions by blending industrial wood chips with Scots pine cones in varying proportions (25 %, 50 %, 75 % and 100 %) and usingr urea formaldehyde glue. The adhesice mixture contained 55 % urea formaldehyde glue and 33 % ammonium chloride as a hardener. Te production parameters included a press temperature of 150 °C, a press time was 7 minutes, and a press pressure of 2,4 MPa to 2,6 MPa. The resulting boards had a thickness of 16 mm and a density ranging from 730 kg/m3 to 740 kg/m3. Tests for thickness iswelling, water absorption, , bending strength, modulus of elasticity and tensile strength perpendicular to the surface were conducted. Results showed that the physical and mechanical properties of the boards containing up to 25 % Scots pine cone met the required standards.